2006
DOI: 10.1139/z05-186
|View full text |Cite
|
Sign up to set email alerts
|

Environmental complexity reduces tadpole predation by water bugs

Abstract: We assessed the role of habitat structure in the outcome of predation by measuring how aquatic vegetation influences predation rates of water bugs (Belostoma oxyurum (Dufour, 1863), Hemiptera, Belostomatidae) on tadpoles of Dendropsophus minutus (Peters, 1872) and Scinax curicica Pugliese, Pombal, and Sazima, 2004 (Anura, Hylidae). Considering that previous studies have shown that some tadpole species preferentially use microhabitats with aquatic vegetation at sites in southeastern Brazil, we hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 23 publications
2
73
0
5
Order By: Relevance
“…This pattern was also confirmed by the laboratory experiment. The Heteroptera used in the experiment are a crucial and typical element of littoral macrofauna, and hence the results of the experiment are indicative of the important role of all predatory insects in the shallow water of the littoral, especially in the water/land contact zone, in shaping the zooplankton population (Murdoch et al, 1984;Kopp et al, 2006;Bourkal, 2012, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern was also confirmed by the laboratory experiment. The Heteroptera used in the experiment are a crucial and typical element of littoral macrofauna, and hence the results of the experiment are indicative of the important role of all predatory insects in the shallow water of the littoral, especially in the water/land contact zone, in shaping the zooplankton population (Murdoch et al, 1984;Kopp et al, 2006;Bourkal, 2012, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason it was very difficult to determine the level of predation pressure exerted by Heteroptera on planktonic crustaceans in the shallow littoral. Previous observations have devoted much attention to the Notonectidae, which have a significant influence on the regulation of water invertebrates and even young fish and amphibians (Louarn and Cloarec, 1997;Kopp et al, 2006;Vandekerkhove et al, 2012). It has been demonstrated that they can be effective regulators of mosquitoes and help to control them, and that, if necessary, they can also feed on Chironomidae (Saha et al, 2008(Saha et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of predation impact on prey may strongly depend on habitat structural complexity (Murdoch and Oaten 1975;Schmidt 1999), which can aVect prey in two ways: more complex habitats may oVer prey more refugia (Hixon and Beets 1993), or they may hamper the predator's ability to detect and catch prey (Warfe and Barmuta 2004; Andruskiw et al 2008;Lecomte et al 2008). For example, the survival of two vole species, Microtus pennsylvanicus and Microtus ochrogaster, was dependent on the structure and cover provided by vegetation (Getz et al 2005), and the presence of aquatic vegetation increased tadpole survival of two anuran species in the presence of predatory water bugs (Kopp et al 2006). Many prey species tend to Communicated by Janne Sundell.…”
Section: Introductionmentioning
confidence: 99%
“…Although several investigations have shown how prey density and habitat complexity may influence predator-prey interaction (Sherratt and Harvey 1989;Hews 1995;Kopp et al 2006), there is lack of information regarding the effect of diel rhythms on predator-prey interactions. Anuran tadpoles and aquatic insects have been employed as model organisms for the analyses of predator-prey interactions.…”
Section: Introductionmentioning
confidence: 99%